Diversity of tree and shrub species in woodlands of Guijeh-bel region of Ahar - Sajjad Ghanbari (تحقیقات جنگل و صنوبر ایران, 2018)
Understanding of biodiversity status can be applied as a guide to better ecosystem management. The ecosystem ecological sustainability is ensured by high species diversity and better conservation. Therefore, the purpose of this research is to identify the species diversity of trees and shrubs in the Guijeh-bel region of Ahar and to determine species diversity using related indicators, as well as the relationship between biodiversity and physiographic factors. Sampling was done in 48 circular sample plots, each 314m2, by a random-systematic method within a 150×200m network. In each sample plot, a list of all of tree and shrub species with abundant-overcome values was recorded based on the Brown Blanche scale. The results showed that there were 13 woody species. Smilax excelsa L. and Rhamnus sp. had the highest (39%) and the lowest (0.04%) presence in the sample plots, respectively. The number of stems varied from 10 to 110 stems of different species in the sample plots. Two index species of Arasbaran region, Acer campestre L. and Viburnum lantana L., were observed in this area. Viburnum lantana and Acer campestre were often found on the western and the eastern aspects, respectively. The main effects of slope on the Taxa, Simpson, Shannon-Weiner and Margaleff indicators were not significant. The main effect of aspect was significant on the taxa index at 1% level and on other indicators at 5% level. The average of all indicators of diversity in the western aspect was higher than those of other aspects. The results of clustering of vegetation composition confirmed the results of the comparison of the site diversity indices. According to the results of the coefficient of variation, the taxa and Margalaf indices had the highest coefficient of variation. Therefore, in other studies, as well as assessment of the effects of management and monitoring of vegetation changes, it is recommended to use the indicators. Based on the results of this study, the high values of slope steepness and biodiversity, provides the protection of the area.